A systematic review of the complications of high-risk third molar removal and coronectomy: development of a decision tree model and preliminary health economic analysis to assist in treatment planning. Issue 9 (November 2020) - Pitros, P.; O'Connor, N.; Tryfonos, A.; Lopes, V.
Abstract: Coronectomy is an alternative surgical technique for the management of high-risk third molars. It involves the removal of the crown of a tooth and the deliberate retention of the roots, thereby avoiding injury to the inferior alveolar nerve (IAN). Previous studies have suggested that it reduces the risk of nerve injury when compared with surgical extraction. The purpose of this study was to systematically review the incidence of complications following coronectomy such as IAN injury, pain, dry socket, infection, root migration, and need for re-operation. A comparative cost analysis of coronectomy and surgical extraction was done based on the results of the review. This provides an insight into the economic implications of the two procedures. A search through the MEDLINE database via Ovid, PubMed, Scopus, EMBASE via Ovid, and Web of Science, was carried out to extract randomised and non-randomised controlled trials. Four studies fulfilled the inclusion criteria. A meta-analysis was conducted to measure the overall effect of each outcome. The pooled odds ratio (OR) for IAN injury was 0.16 (95% CI 0.01 to 0.39). Coronectomy reduced this risk by 84%. Dry socket may occur less frequently following coronectomy whereas infection did not show a higher incidence with either intervention. Root migration was found to occur in 13%–85% of cases and the average incidence of re-operation was 2.2%. The ratio of the average costs was 1.12 favouring coronectomy if cone-beam computed tomography (CBCT) was not done prior to the procedure. If a scan was taken routinely for coronectomy, the cost ratio marginally favoured extraction. Coronectomy reduced the risk of nerve injury in high-risk third molars. Definitive conclusions, however, cannot be made for outcomes such as the need for re-operation, which may alter the cost ratio of coronectomy:extraction, as higher quality studies with longer follow-up are needed.